Controller design via model order reduction for interval systems using Kharitonov theorem and Nevalinna-pick theory: a case study. (14th September 2021) - Chauhan, Dharma Pal Singh; Singh, V.P.
This manuscript describes a new procedure to design a controller for unstable high order interval systems using model order reduction and Nevalinna-pick theory. In this process, First, a high-order unstable interval system is converted into a reduced-order model in which improved Routh table truncation and time-moment matching techniques are applied. The denominator and numerator of reduced- order model are evaluated by improved Routh table truncation and time-moment matching technique, respectively. Next, employing the Kharitonov theorem and Nevalinna-pick theory, controller is designed for a reduced-order model in a certain range of uncertainty. To explain the procedure, the proposed method is applied to the fourth-order unstable interval system. Results prove the effectiveness of the method.